IDENTIFIKASI KESULITAN BELAJAR DAN PENYUSUNAN PROGRAM BIMBINGAN BELAJAR SISWA KELAS X SMA NEGERI 5 PONTIANAK - Yudistira, Indra; Wicaksono, Luhur; Lestari, Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Learning difficulties are the existence of a distance between expected academic achievement and academic achievement, which is caused by a disturbance in a psychological process or more, so that it is said to have learning difficulties if the specified time limit does not reach a measure of understanding of learning material. Tutoring program is a program that provides services to students to develop their personality and self-adjustment to their duties as a lesson, in which planning needs to be determined who will provide services and what is needed for the implementation of the tutoring program itself. The method used is descriptive method. This study uses a quantitative approach. The population in this study were 326 and the sample was 82 students of SMAN 5 Pontianak. Data collection techniques used are indirect communication techniques and data collection tools with questionnaires. While the data analysis technique uses a percentage formula. Based on learning difficulties found, a tutoring program was developed to overcome student learning difficulties.Â Keyword: Learning Difficulties, Consultation Programme